We Were All Once Young: Reducing Hostile Ageism From Younger Adults' Perspective - Chen, Zizhuo; Zhang, Xin (Frontiers in Psychology, 2022)
The worldwide spreading pandemic, COVID-19, has caused hostile ageism towards older adults. We adopted a new intervention to reduce such hostile ageism. “Imagine that they were Young” referred to the imagination of what an older adult might look like, think and behave when he or she were once young, which was a reversed but a refined intervention of the widely-used method of “Imagine that you were old”. In the present study, intergenerational tension was primed, and then 205 younger adults in China aged 18 to 37 were randomly assigned to 3 different conditions (“Imagine that they were Young”, “Imagine that you were old” and control condition), asking them to imagine (and then write down) once older adults were young, or a future aging self, or read an unrelated essay respectively as experimental manipulations. Then they should distribute medical funds worthy of 1 million Chinese Yuan to two COVID-19 patients of 25 and 85 years old indicating their attitudes toward older adults (or hostile ageism). At last, we measured their general attitudes and stereotypes towards older adults. Results verified the effectiveness of both interventions, such that younger adults who took either intervention distributed more medical funds and showed more positive aging attitudes towards older adults than those in the control group. Moreover, “Imagine that they were Young” was tested to be even more effective than “Imagine that you were old”. A series of relative mediation models revealed that the stereotype of warmth mediated the effect for both interventions on decreased hostile ageism behaviors, compared with the control condition. While “Imagine that they were Young” could additionally reduce hostile ageism through a higher level of “including the older adults in their self-group (the young)”. This new intervention provided a more effective and practicable way to eliminate hostile ageism.